A REVIEW OF THE MINGLE MODEL AS A NEW TECHNIQUE IN TEACHING SPEAKING: INDONESIAN CONTEXT - Rahman, M Arinal; Ja?afar, Hashimah (LET: Linguistics, Literature and English Teaching Journal, 2017)
The mingle model is a new technique to teach speaking that is developed by Darmayenti (2015). Few scholars have investigated the relation, contribution, and implementation of a mingle technique in class. This paper aims to discuss the constraints of the mingle model from Darmayenti (2015) in improving students? speaking skills. Based upon few relevant journal articles, the effects of content evaluation display limitation of research on the integrated effect of the mingle model. This paper provides information for future studies to expose the effectiveness of the Mingle model on students'? speaking skills proficiency.